Romances de operárias: vida e trabalho nas fábricas de Horizonte - Ceará - Drumond, Nágyla Maria Galdino (2019)
The present research analyzes the culture (way of life) and the work among women operating in the industrial civilizing processor in the city of Horizonte, Ceará. Horizonte is a city in the Metropolitan Region of Fortaleza, located 40 km from the capital of Ceará, home to industries such as footwear, textile and food industries. In the last 25 years, as part of the not industrialization of Fortaleza, the city is an industrial center with profound transformations in the physical, socialand economic landscape of the region, presenting more than 80% of its population in an urban area. The research traces the trajectories of the experiences of women workers in the largest footwear industry in the city, investigating the transition between the agricultural way of life and the industrial way of life. Systematic visits to the city, participant observation in multiple moments of the daily routine of the final interlocutors, semi-structured interviews and bibliographical review on the concepts of culture as a way of life, gender and work gave the theoretical and methodological north of the research. The choicefor a sociological novel came from the perspective of presenting the final interlocutors of research individually, while at the same time highlighting in their narratives the analytical keys that dialogue in the understanding of new cultural forms in social life mediated by work in the factory. Along the thesis, to each presented character - Matilde, Rosinha, Octavia and Aurora - the constitutive elements of this new way of life among the local working class are approached.The thesis is about the multiple imbrications between culture, gender, work and time in the formation of Pagu, Ser- Operária, protagonist of this plot and sociological portrait of the industrial civilizing process in Horizonte / Ceará.